PENGEMBANGAN PERANGKAT PEMBELAJARAN KURIKULUM MERDEKA MODEL INKUIRI TERHADAP KEMAMPUAN PENALARAN FORMAL SISWA PADA MATERI PENGGUNAAN MIKROORGANISME DALAM BIOTEKNOLOGI KELAS X MA’MUALIMMAT NWDI KELAYU - Ariandani, Nunung (Cocos Bio, 2023)
This research aims to: (1) Develop Merdeka Curriculum Learning Inquiry Model for Students' Formal Reasoning Abilities, (2) To examine the suitability of Merdeka Curriculum Learning Inquiry Model for Students' Formal Reasoning Abilities, (3) To find out the validity of Merdeka Curriculum Learning Inquiry Model on Students' Formal Reasoning Ability. This development research uses a 4D model which is carried out in 4 stages; definition, design, development and dissemination. The test subjects in this research were material experts, design experts, biology teachers, and 19 MA Mu'Alimmat NWDI Kelayu students. The data collection technique uses a questionnaire and the data is analyzed using quantitative descriptive analysis techniques. Based on the results of data analysis and discussion, the independent curriculum learning device product with an inquiry model on students' formal reasoning abilities is feasible and valid for use in teaching and learning activities. This feasibility can be seen from the average feasibility score obtained from material experts 4, design experts 3.45, biology teachers 3.33, and student responses 3.44. This has good and very good criteria. Furthermore, the validity of the independent curriculum learning tools can be seen from the ideal percentage of material experts 100%, design experts 86.25%, biology teachers 83.33%, and student responses 86.57%. Based on the percentage of ideality, the results obtained have valid and very valid criteria. Based on the results of the average percentage for students' formal reasoning level, it is in the good category.